Abrupt Contraction of the Indo‐East Asian Monsoons Ended the Holocene Humid Period. Issue 22 (21st November 2022) - Goldsmith, Yonaton; Xu, Hai; Torfstein, Adi; Lan, Jianghu; Song, Yunping; Zhang, Jin; Zhou, Kang'en; Cheng, Jun; Enzel, Yehouda
Abstract: Rain‐belt migration, and in particular monsoon migration, are a cardinal, yet under‐constrained aspect of climate change. Here, we present a new lake‐level record from a closed‐basin lake in northern China and a compilation of available lake level records from closed‐basin lakes located at the northern margins of East Asian and Indian monsoon regions. These data show that ca. 6 ka ago, changes in water availability, as recorded by the surface areas of the closed‐basin lakes, shrunk dramatically, within a few decades, and have not been restored to their pre‐6 ka sizes since. These data imply that the Indo‐East Asian monsoon systems underwent a large coeval southward contraction, which preceded the gradual decline in insolation forcing, and abruptly ended the Holocene Humid Period (HHP). This new compilation enables to constrain potential feedback mechanisms involved in the early termination of the HHP at the monsoon fringes. Plain Language Summary: A cardinal question in climate research is how and why rain‐belts shift under different climatic conditions. Here we show, that ∼6, 000 years ago the surface areas of nine closed‐basin lakes located at the northern margins of the East Asian and Indian monsoon regions shrunk dramatically, within a few decades, and have not been restored to their pre‐6 ka sizes since. These data suggest that an abrupt, large scale, southward contraction of the Asian monsoons ended the Holocene Humid Period, and caused large scale desertification at the monsoonal fringes. Key Points: Lake‐levels of closed‐basin lakes at Asian monsoon margins were high during the early‐middle Holocene and dried out abruptly ∼6 ka ago A lake‐level record from north China provides unprecedented age and rate resolution of monsoon decline at Holocene Humid Period termination Asian monsoon margin lakes dried out earlier then vegetation change thus, "vegetation feedback" was not a leading factor of monsoon decline